IOT based control of DC traction motor (International Journal of Engineering and Computer Science, 2017)
In this paper, the IOT based control of DC traction motor has been reported. Internet is the most widely used, high speed and easily accessible communication medium in the modern day world. The proposed system allows any person from any corner of the world to control heavy industrial machines. The proposed system is simple and highly effective in terms of cost and efficiency. In this system, the switching and the speed of the DC motor can be controlled by using a self-developed android application. The PROTEUS simulation confirmed the theoretical estimates of the performance of the proposed system.